The Impact of Liberalized Concealed Carry Laws on State Homicide Rates - K. Alexander Adams (Journal of Liberty and International Affairs)
Liberalized concealed carry laws test how firearm legislation affects crime in the US. This study analyzes the relationship between these laws, total homicide, and firearm homicide using panel data from 1980 to 2018 across all 50 states and the District of Columbia. The analysis uses multivariate regression with state and time-fixed effects and applies a general-to-specific procedure to select control variables. Robustness checks, including a generalized synthetic control model, confirm the findings. The results show no statistically significant relationship between shall-issue or permitless carry laws and homicide rates, even at the 10% level. The findings remain consistent across alternative model specifications. If these effects are truly null, liberalized concealed carry laws may have positive social implications, offering valuable insights for policymakers.